An Encounter With the Other: A Thematic and Content Analysis of DMT Experiences From a Naturalistic Field Study - Michael, Pascal; Luke, David; Robinson, Oliver (Frontiers in Psychology, 2021)
Introduction: N, N-Dimethyltryptamine (DMT) is an endogenous serotonergic psychedelic capable of producing radical shifts in conscious experience. Increasing trends in its use, as well as new trials administering DMT to patients, indicate the growing importance of a thorough elucidation of the phenomenology the drug may occasion. This is particularly in light of the hyper-real, otherworldly, and often ontologically challenging yet potentially transformative, nature of the experience, not least encounters with apparently non-self social agents. Laboratory studies have been limited by clinical setting and lacking qualitative analyses, while online surveys’ limitations lie in retrospective design, recreational use, and both of which not guaranteeing ‘breakthrough’ experiences. Methods: We report on the first naturalistic field study of DMT use including its qualitative analysis. Screened, healthy, anonymised and experienced DMT users (40-75mg inhaled) were observed during their non-clinical use of the drug at home. Semi-structured interviews using the micro-phenomenological technique were employed immediately after their experience. This paper reports on the thematic analysis of one major domain of the breakthrough experiences elicited; the ‘other’. Thirty-six post-DMT experience interviews with mostly Caucasian (83%) males (8 female) of average 37 years were predominantly inductively coded. Results: Invariably, profound and highly intense experiences occurred. The main overarching category comprised the encounter with other ‘beings’ (94% of reports), with further subordinate themes including the entities’ role, appearance, demeanour, communication and interaction; while the other over-arching category comprised experiences of emerging into other ‘worlds’ (100% of reports), in turn consisting of the scene, the content and quality of the immersive spaces. Discussion: The present study provides a systematic and in-depth analysis of the features of the otherworldly encounter within the breakthrough DMT experience, as well as elaborating on the resonances with both previous DMT studies and other types of extraordinary experiences which also entail entity encounters. These include the alien abduction, folkloric, shamanic and near-death experience. Putative neural mechanisms of these features of the DMT experience and its promise as a psychotherapeutic agent are discussed in light of such findings.